The Duel for Existenz An Existential Reading of Arturo Pérez-Reverte’s The Fencing Master (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
The present paper represents an existential reading of Arturo Pérez-Reverte's novel The Fencing Master by means of Karl Jasper's (1970) concepts of Existenz and Gabriel Marcel's (2002) notion of creative fidelity. Particular emphasis is given to the protagonist's struggle for transcendence, his encounter with boundary situations and the possibility of unconditional action and existential communication. The paper is also written in the spirit of the philosophy of Gilles Deleuze and Félix Guattari (1986), making literature work towards the enhancement of life and the exploration of our possibilities for self-becoming. In this respect, what follows is a particular reading of a fictional text and not its interpretation.